The Question of Life and Death by Cicero and Macrobius - Tóth, Orsolya (Acta Classica Universitatis Scientiarum Debreceniensis, 2026)
To Cicero’s Somnium Scipionis Macrobius prepared a Neoplatonic commentary in Late Antiquity. On the grounds of these two works and Cicero’s other political or philosophical writings and letters this study seeks an answer to the question what similarities and differences can be demonstrated between the two authors’ way of thinking as regards the nature of the virtues, the issue of vita activa and vita contemplativa, the meaning of life and the necessity of voluntary death.